Structural and optical properties of dense vertically aligned ZnO nanorods grown onto silver and gold thin films by galvanic effect with iron contamination. (May 2015) - Scarpellini, D.; Paoloni, S.; Medaglia, P.G.; Pizzoferrato, R.; Orsini, A.; Falconi, C.
Graphical abstract: Highlights: ZnO nanorods were grown on Au and Ag films in aqueous solution by galvanic effect. The method is prone to metal contamination which can influence the ZnO properties. Iron doping improves the lattice matching between ZnO and the substrate. Energy levels of point defects are lowered and the light emission is red-shifted. Galvanic-induced nucleation starts and proceeds continuously during the growth. Abstract: Dense arrays of vertically aligned ZnO nanorods have been grown onto either silver or gold seedless substrates trough a simple hydrothermal method by exploiting the galvanic effect between the substrate and metallic parts. The nanorods exhibit larger bases and more defined hexagonal shapes, in comparison with standard non-galvanic wet-chemistry synthesis. X-ray diffraction (XRD) shows that the iron contamination, associated with the galvanic contact, significantly improves the in-plane compatibility of ZnO with the Au and Ag cubic lattice. Photoluminescence (PL) measurements indicate that the contamination does not affect the number density of localized defects, but lowers their energy levels uniformly; differently, the band-edge emission is not altered appreciably. Finally, we have found that the ZnO hetero-nucleation by galvanic effect initiates at different times in different sites of the substrate area. Our results can be useful for the fabrication of high performance piezonanodevices comprising high-density metal-to-ZnO nanoscaled junctions without intermediate polycrystalline layers.